Analysis of Community Trust Formation Agains UPN “Veteran” East Java - Muslimin; H. Pudjo (Future Science)
At present the study of factors influencing public trust in Higher Education in Indonesia has received enough attention from researchers to conduct a more in-depth study so that decisions taken by Higher Education are on target. Therefore, the trust of the public as consumers of Higher Education services is an important thing that needs to be known by the Higher Education with the aim of knowing what things are affecting people's trust in loyalty to UPN College